The utility of student interest in a particular specific program, presentation in professional meetings, and open science collaborative writing in mastering health management and policy tools in MPH training - Mawarni, Dian; Maula, Ahmad Watsiq; Hasanbasri, Mubasysyir (BKM Public Health and Community Medicine, 2021)
ies Trying out a presentation in a professional symposium is difficult for a beginner. Even novice writers have difficulty imagining what they will tell conference attendees. They even have difficulty distinguishing what questions they want to be answered and shared in scientific meetings. For example, they find it difficult to focus on something general (conceptual) or specific (operational); specific case stories different from others, failed cases, or best practice cases. This paper explores the importance of observing a preferred program and the potential of an open science approach in overcoming the difficulties of students and lecturers in starting their development as professionals. The primary failure of beginners is that they do not yet have a collection of one type of program from various countries, which they collect from day to day by comparing with each other. The second failure is that they do not have a discussion partner, which makes them open to finding hot points from their program, encouraging them to explore more exciting things. We emphasize that programming games and creating class assignments through an open science approach should be a writing strategy for students who analyze and apply the theory and framework of projects to help improve health programs in the field.